The Impact Of Farmland On The Income Of Farmers In Morokay Village, Central Maluku Regency - Muhammad Syahroni; A. E. Pattiselanno; N. F. Wenno (International Journal of Economics, Business and Innovation Research, 2023)
The study aims to find out and know how the fields of horticultural rice plants affect the farmer's income. The sample retrieval technique used was by an impressive. sample used by a total of 33 people. The data collected is secondary and primary. The method of data analysis used is qualitative and quantitative descriptive analysis. Analysis shows that since the land functions of horticultural rice plants have a positive effect on farmers' income in morokay village, the farmers' average income from rice plants is Rp 9,237,682, and after raising the horticultural land's average value increases to Rp 33,923,348